Muhammad Abduh's Typical Modern Education: His Thoughts and Reforms in the Islamic World - Hafizh, Muhammad; Munawir Hasan; Abdul Aziz Shutadi; Yan Nurcahya; Rahardja, Muhammad Nurfaizi Arya (Pascasarjana IAIN Metro, 2025)
In this modern era, everything is required to transform to suit the times. Likewise regarding education, in this era of continuous development, Islamic education is required to always develop to adapt to the times as attempted by Muhammad Abduh. Muhammad Abduh was an initiator of Islamic education reform who came from Egypt. This research is qualitative in nature and the data was obtained using the library research method. The data obtained was then analyzed using descriptive-analysis techniques. The results of this research will explain Muhammad Abduh's ideas regarding the renewal of Islamic education, namely (1) The aim of education is to educate the mind and soul and convey it to the limit of a person's possibility of achieving happiness in this world and the hereafter, (2) Muhammad Abduh aims to harmonize between general knowledge and religious knowledge, (3) Divide education into 3 levels (Primary Education, Secondary Education, Upper Education), (4) Each level has its own curriculum, (5) Divide educational methods into two, namely micro methods which are centered on teaching methods and macro methods which are systems where schools have an organizational structure where each division will influence each other, (6) Education without distinguishing gender.